Methodologies for Fostering Critical Thinking Skills from University Students' Points of View - Lucía Campo; Héctor Galindo-Domínguez; María-José Bezanilla; Donna Fernández-Nogueira; Manuel Poblete (MDPI AG, 2023)
Developing critical thinking skills appears to be a challenge for higher education institutions. However, little is known about the students' points of view regarding the methodologies they consider to foster the development of this competence. To answer this question, a total of 263 Spanish university students participated in this study and were asked what they understood by critical thinking and the methodologies they considered to be the most effective for developing it. The results indicated that, based on students' points of view, there were six methodologies that mainly contributed to developing critical thinking: Debates, project-based learning, practices in real contexts, doing research, cooperative learning, and case studies. These results were unanimous regardless of the student's understanding of critical thinking: Analyzing/organizing, reasoning/arguing, questioning/asking oneself, evaluating, taking a position/taking a decision, compromising/acting. These findings have important theoretical and practical implications for teachers and educational institutions in relation to the development of critical thinking in higher education.